PELAKSANAAN PENDIDIKAN AGAMA ISLAM MELALUI KEGIATAN OUTBOUND - Imam Wahyudi; Zuhdiyah Zuhdiyah; Sofyan Sofyan (PAI RAFAH, 2022)
This study discusses the Implementation of Islamic Religious Education Through Outbound Activities in the Bukit Siguntang Indonesian Nature School in Palembang. This research is motivated by PAI learning activities that still look monotonous and lack innovation. Outbound types of games that must be adjusted to the subject matter as well as outbound games that can eliminate the seriousness of learning. The purpose of this study is to be able to know the Implementation of Islamic Education through Outbound activities at the Indonesian Nature School in Bukit Siguntang Palembang and the Supporting and Inhibiting Factors. The type of research used is Field research or Field Research that uses a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. The data analysis method used is the Miles and Huberman analysis method using the Stages of data reduction, data presentation, and conclusions. The results showed that: the implementation of Islamic Religious Education through outbound activities at the Indonesian Natural School in Bukit Siguntang Palembang was through three stages, namely the planning phase, the implementation phase, and the reflection stage. The planning stage starts with lesson plans and weekly plans. The implementation stage begins with the division of groups, the explanation of game procedures, and the process of carrying out activities. At the reflection stage, students learn from outbound activities. Supporting factors are (1) the school environment (2) enthusiastic students (3) complete equipment. While the inhibiting factors are: (1) weather conditions (2) time (3) the state of students